How Can Hypnodontics Manage Severe Gag Reflex for Root Canal Therapy? A Case Report - Ramazani, Mohsen; Zarenejad, Nafiseh; Parirokh, Masoud; Zahedpasha, Samir (Iranian Endodontic Journal, 2016)
In endodontics, severe involuntary gagging can have a severe impact on treatment procedure. There are many ways to ease the gag reflex, one of which is hypnosis. A 34-year-old male was referred for root canal treatment of a molar tooth. He had not received any dental treatments for the past nine years due to fear of severe gag reflex. Three hypnotic sessions based upon eye fixation, progressive muscle relaxation and guided imagery techniques were spent for psychosomatic management. The gag reflex was controlled and reduced to a normal level, and the required dental treatments including root canal therapy and restoration were performed successfully. This report shows that hypnosis can control gag reflex for dental treatments. Keywords: Dental Treatment; Endodontics; Gag Reflex; Hypnosis; Root Canal Therapy